Motivation as a Moderator in the Relationship between Work-Life Balance and Employee Performance - Budiarto Ilyas (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
This study aims to analyze the determinants of personnel performance by examining the influence of work-life balance and job satisfaction and evaluating the role of motivation as a moderation variable in these relationships. Using a quantitative approach with Structural Equation Modeling analysis techniques based on Partial Least Squares or SEM PLS, this study involved 180 personnel of the Southeast Sulawesi Regional Police (POLDA) Sulawesi as respondents selected through structured sampling techniques. The results of statistical analysis provide empirical evidence that work-life balance has a positive and significant influence on both job satisfaction and employee performance directly. On the other hand, the findings of the study show that motivation partially does not have a significant influence on performance, but it has been shown to play a vital role as a moderation variable that strengthens the relationship between variables in the model. In addition, job satisfaction was identified as a strong mediator in bridging the influence of work-life balance on personnel work results. The conclusion of this study confirms that to optimize performance in a stressful police environment, synergy between proportionate work balance policies and the creation of a satisfactory environment is needed because the motivation of new personnel will effectively impact performance when supported by adequate psychological and well-being conditions.